2012
DOI: 10.1521/soco.2012.30.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Time: Moral Emotions Appear More Intense with Temporal Distance

Abstract: How intense do people expect their future emotional reactions to be? This should depend on the fit between the social perspective (near vs. distant) involved in the emotion and the emotion-eliciting event's temporal distance. Temporal distance and social distance are interrelated . We therefore argue that people should anticipate experiencing emotions that involve taking a socially distant perspective (e.g., guilt and shame in contrast to pleasure and sadness) with greater intensity when they predict their emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Out of these, 13 studies showed empirical evidence that representing objects or events as high-level construals or as psychologically distant is directly associated with stronger moral judgments and increased moral behavior (Agerström & Björklund, 2009a, 2009bAgerström, Björklund, & Carlsson, 2012Choi, Park, & Oh, 2012;Eyal et al, 2008;Napier & Luguri, 2013;Nordhall & Agerström, 2013;Rixom & Mishra, 2014;Tumasjan, Strobel, & Welpe, 2011;van Houwelingen, van Dijke, & de Cremer, 2015;Yi, Charlton, Porter, Carter, & Bickel, 2011). Two studies showed opposing results such that low-level construals and psychological proximity elicited stronger moral judgment and increased moral behavior (Gong & Medin, 2012;Lammers, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, 13 studies showed empirical evidence that representing objects or events as high-level construals or as psychologically distant is directly associated with stronger moral judgments and increased moral behavior (Agerström & Björklund, 2009a, 2009bAgerström, Björklund, & Carlsson, 2012Choi, Park, & Oh, 2012;Eyal et al, 2008;Napier & Luguri, 2013;Nordhall & Agerström, 2013;Rixom & Mishra, 2014;Tumasjan, Strobel, & Welpe, 2011;van Houwelingen, van Dijke, & de Cremer, 2015;Yi, Charlton, Porter, Carter, & Bickel, 2011). Two studies showed opposing results such that low-level construals and psychological proximity elicited stronger moral judgment and increased moral behavior (Gong & Medin, 2012;Lammers, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A study focusing on the emotional underpinnings of moral judgment in relation to CLT was conducted by Agerström et al (2012). The results of this study showed that when people predict their reactions to temporally distant events, they experience moral emotions (e.g., guilt, shame) more intensely than when they predict their reactions to temporally close events.…”
Section: Abstract Thinking Leads To Stronger Moral Judgmentsmentioning
confidence: 94%
“…Although we did vary our manipulation somewhat across studies, other variations could manipulate vicarious [16], or collective guilt [17], or examine whether the anticipation of future guilt shows similar, weaker, or stronger effects [37], [38]. Finally, in Study 4 we examined how the weight of guilt affected perceptions of effort to complete physical acts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research has explored psychological distance in the context of recycling (Agerström & Björklund, 2009a;Agerström, Björklund, & Carlsson, 2012;Fessel, 2011) and environmental concerns (Agerström & Björklund, 2009a). This research has, however, been limited to the exploration of temporal distance (Agerström & Björklund, 2009a;Agerström et al, 2012;Fessel, 2011), social distance (Agerström et al, 2012), moral dilemmas (Agerström & Björklund, 2009a;Agerström et al, 2012), anticipated (Agerström & Björklund, 2009a or self-reported behaviour (Fessel, 2011). Furthermore, research has highlighted the potential social bias in self reported environmental behaviour (e.g., Auger & Devinney, 2007;Beckmann, 2005).…”
Section: Introductionmentioning
confidence: 99%